Macroscopic orientation of natural and model membranes for structural studies. - Gröbner, G; Taylor, A; Williamson, P; Choi, G; Glaubitz, C; Watts, J; de Grip, W; Watts, A (1997)
One approach for obtaining high-resolution structural and functional information for biomembranes and their proteins is by static solid-state NMR of oriented systems. Here, a general procedure to align fully functional biological membranes containing large membrane proteins (Mr >30,000) is described. The method, based on the isopotential spin-dry ultracentrifugation technique, relies on the centrifugation of membrane fragments onto a support with simultaneous, or subsequent, partial evaporation of the solvent which aids alignment. The quality of orientation, as shown by the mosaic spread of the samples, was monitored by static solid-state 31P NMR for the phospholipids and by 2H NMR for a deuterated retinal in bovine rhodopsin. The generality of this method is demonstrated with three different membranes containing bovine rhodopsin in reconstituted bilayers, natural membranes with the red cell anion exchange transport protein in erythrocytes, band 3, and the nicotinic acetylcholine receptor.